Lise Lachmann og kjærligheten - Kristiansen, Bjørn H.S. (Tidsskrift for kulturforskning, 2003)
This article tells the tragic story of an upper-class woman who lived in Christiania between 1769-1823. The sources to Lise Lachmann’s life are few and fragmentary, they only give a glimpse into what was a complex situation. Lise Lachmann married twice. The first marriage was arranged by her parents, while the second was a result of her own feelings. Lise Lachmann struggled throughout her life, and she emerges from the material as an individual in changing social positions and roles. An important source for this story is the memoirs of Conradine Dunker who, in addition to a sharp memory, suffered a fate not too different from Lise Lachmann’s. Both women embraced the new ideas on love and tried to put them into life by marrying the one they loved and against the wish of their parents. In a culture there is room for a certain degree of individual freedom to strech the limits of the norms, but it is not permittable to trespass them. Lise Lachmann went beyond what could be accepted while Conradine Dunker did not. Both of them, however, payed a high price for their love.